(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Personal authentication that correctly identifies valid users in an indispensable security technology for enabling people to enjoy the access to data services with a sense of confidence and assurance. Passwords have been extensively used to identify authorized users in the past, but passwords alone are vulnerable because people tend to choose weak password relating to some aspect of them (e.g. birthday, phone number, family name) that can be guessed. This has led to growing interest in biometric authentication using fingerprints that make it possible to identify personal authentication correctly. It eliminates problems of forgotten passwords or lost cards and is currently becoming more popular for convenient and secure authentication. NTT Microsystems is a new and exclusive technology that overcomes the limitations of previous systems and sets a new standard for compact, reliable and low-cost fingerprint authentication. NTT laboratories have developed Finger Token, a portable fingerprint identification device that substitutes a fingerprint instead of password for authentication